2017
DOI: 10.1515/jpem-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dyslipidemia and associated factors in children and adolescents with type 1 diabetes

Abstract: Background: Dyslipidemia increases the frequency and severity of micro and macrovascular complications of type 1 diabetes (T1D). The present study aims to determine the prevalence of dyslipidemia and its association with clinical and laboratory findings in diabetic children and adolescents. Methods: The study included 202 children and adolescents with T1D. Demographic data and laboratory findings were obtained from patients files. Results: Dyslipidemia prevalence was found to be 26.2%. Hypercholesterolemia (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 43 publications
5
43
1
Order By: Relevance
“…Type 1 DM (T1DM), if well controlled with insulin, is associated with only a few if any aberrations of lipid metabolism [11]. Indicatively, high low-density lipoprotein cholesterol (LDL-C) was found in 15.8% and high triglyceride-rich lipoproteins (TGLs) in 12.9% in a cohort of young T1DM subjects [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 1 DM (T1DM), if well controlled with insulin, is associated with only a few if any aberrations of lipid metabolism [11]. Indicatively, high low-density lipoprotein cholesterol (LDL-C) was found in 15.8% and high triglyceride-rich lipoproteins (TGLs) in 12.9% in a cohort of young T1DM subjects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 DM (T1DM), if well controlled with insulin, is associated with only a few if any aberrations of lipid metabolism [11]. Indicatively, high low-density lipoprotein cholesterol (LDL-C) was found in 15.8% and high triglyceride-rich lipoproteins (TGLs) in 12.9% in a cohort of young T1DM subjects [11]. Only in patients with poorly controlled T1DM and in those liable to develop obesity or metabolic syndrome (MetS) does DD manifest in a form similar to that linked to T2DM [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from Iran, the ratio of dyslipidemia among 274 T1DM patients was 74.8% and it was shown that the majority dyslipidemia developed was hypercholesterolemia, and hypertriglyceridemia was less frequently [13]. In a study from Turkey, the rate of dyslipidemia in patients with T1DM was found to be 26.2% with a high prevalence of hypercholesterolemia and hypertriglyceridemia [14]. A possible explanation of variation reports includes multiple genetic factors in different ethnic groups, the diet and physical activity of the general population, and different laboratory methods [15][16].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, diabetes rates are increasing epidemiologically by 2-5% per year in Europe, Middle East, and Australia whereas some central and eastern European countries demonstrate an even more rapid increase up to 9% [2]. In patients with T1DM, chronic complications including nephropathy, neuropathy, retinopathy, peripheral vascular, and cardiovascular diseases (CVD) directly affect the expectancy and long term quality of life [3]. The presence of dyslipidemia increases the frequency and severity of these complications [4].…”
Section: Introductionmentioning
confidence: 99%